Large SiO₂ Sizes Influencing Light Scattering Properties in Original White LED Structure - Cong, Pham Hong; Loan, Nguyen Thi Phuong; Lee, Hsiao-Yi (Science and Technology Indonesia, 2026)
Previously, SiO₂ particles (1-10 wt%, <10 µm) were proposed to augment the light flux and correlated color temperature (CCT) deviation in conventional blue-excited LEDs. This research paper explores the application of larger SiO₂ particle sizes within a conventional LED model. SiO₂ particles with diameters ranging from 1 µm to 20 µm were analyzed for their scattering properties using the Stöber method, a Mie-scattering-based MATLAB program, and LightTools software to simulate the optical attributes of a phosphor-transmuted WLED apparatus, supported by XRD, SEM, and other analytical techniques. SiO₂ was integrated into the yellow phosphor YAG:Ce layer to induce scattering phenomena within the active layer. Through our investigation, the concentrations of SiO₂ and YAG:Ce phosphor were consistently maintained at 5 wt% and 10 wt%, respectively. Our findings focus on assessing backward scattering with larger SiO₂ sizes. Modulating the sizes of SiO₂ spheres reduced CCT deviation and enhanced both flux output and color rendering performance. These results emphasize the potential utility of larger SiO₂ particles in enhancing white LED performance and facilitate further investigation to optimize their usability in production processes.